Multi-objective Optimal Allocation of Reactive Compensation and OLTC in Active Distribution Network - Yu TIAN; Jing HUANG; Xiao XIE; Ruoxin WANG; Danqing SHEN; Lina HE; Kaifan YANG; Ruke CHEN (Zhongguo dianli)
In order to cope with the power flow fluctuation of the active distribution network and improve the economy and security of the active distribution network operation, a multi-objective optimal configuration model integrating the investment layer and the multi-period simulation operation layer is established with the goal of minimizing the investment cost, network loss and voltage offset. At the same time, in order to further determine the optimal allocation scheme that meets the actual needs, a dynamic weighted multi-objective solution method is proposed to obtain the optimal solution set. The effectiveness of the proposed method is verified by a simulation example.